The clinical and molecular spectrum of QRICH1 associated neurodevelopmental disorder. Issue 2 (11th December 2021) - Kumble, Smitha; Levy, Amanda M.; Punetha, Jaya; Gao, Hua; Ah Mew, Nicholas; Anyane‐Yeboa, Kwame; Benke, Paul J.; Berger, Sara M.; Bjerglund, Lise; Campos‐Xavier, Belinda; Ciliberto, Michael; Cohen, Julie S.; et al.
Abstract: De novo variants in QRICH1 (Glutamine‐rich protein 1) has recently been reported in 11 individuals with intellectual disability (ID). The function of QRICH1 is largely unknown but it is likely to play a key role in the unfolded response of endoplasmic reticulum stress through transcriptional control of proteostasis. In this study, we present 27 additional individuals and delineate the clinical and molecular spectrum of the individuals ( n = 38) with QRICH1 variants. The main clinical features were mild to moderate developmental delay/ID (71%), nonspecific facial dysmorphism (92%) and hypotonia (39%). Additional findings included poor weight gain (29%), short stature (29%), autism spectrum disorder (29%), seizures (24%) and scoliosis (18%). Minor structural brain abnormalities were reported in 52% of the individuals with brain imaging. Truncating or splice variants were found in 28 individuals and 10 had missense variants. Four variants were inherited from mildly affected parents. This study confirms that heterozygous QRICH1 variants cause a neurodevelopmental disorder including short stature and expands the phenotypic spectrum to include poor weight gain, scoliosis, hypotonia, minor structural brain anomalies, and seizures. Inherited variants from mildly affected parents are reported for the first time, suggesting variable expressivity. Abstract : QRICH1 related neurodevelopmental disorder.